(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
The incorporation of gaming into pedagogy has proven pivotal for bolstering knowledge transfer. A more potent dynamic emerges when the Game-Based Learning (GBL) methodology is interlaced with Competition-Based Learning (CBL). Given that GBL integrates course contents into games and CBL infuses competition into the learning process, their pairing creates a scenario where learning is fostered through competitive educational gaming. This study merges GBL and CBL through the design and development of LetteRush, a mobile word game aimed at English language vocabulary building and spelling proficiency. This paper presents a content analysis of LetteRush, highlighting its conflation of GBL and CBL tenets. Adopting a qualitative, software development-centric research design, the study’s findings corroborate the following: (1) vocabulary and spelling proficiency exercises can be strategically encoded into competitive educational gaming; (2) software-based educational aids like games can be developed locally and cost-effectively; and (3) educational gaming competitions present an innovative, co-curricular channel for reinforcing classroom lessons. Consequently, the study concludes that the integration of such gaming competitions into mainstream education is achievable, warranting concerted research efforts in this direction.